Regional Library Policy (Based on the Example of Yamal-Nenets Autonomous Area) - Tatyana Y. Golubenko; Татьяна Юрьевна Голубенко (Bibliotekovedenie [Library and Information Science (Russia)], 2009)
The article deals with the features of creation of the regional library policy in the Yamalo-Nenetsky autonomous district in the period of administrative reforms in 1994—2008. Рассмотрены особенности формирования региональной библиотечной политики в Ямало-Ненецком автономном округе в период административных реформ 1994—2008 годов.